More on plurality and authorship in science: A reply to Tang. (4th July 2019) - Moffatt, Barton
ABSTRACT: Understanding the "political economy" of the research environment is at the core of getting clear on the ethical aspects of authorship. Questions about who should be an author on a scientific paper are complicated by the fact that authorship is used to determine credit inside science and by outside institutions whose interests and standards often differ dramatically. Much of the research ethics community seeks to impose an elite ethical consensus on scientific fields. I argue that this approach undermines the scientific autonomy of research communities. In contrast, we should develop bottom-up strategies that empower local communities and associations.